Characterization and subtyping of Listeria monocytogenes strains from butcher shops - Londero, Alejandra (2019)
We characterized L. monocytogenes strains isolated from ground beef (n = 40) and butcher shop environmental (n = 99) samples before and after implementing improvement actions. Strains were serotyped and subtyped by enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) and ApaI-pulsed-field gel electrophoresis (PFGE) to establish their epidemiological relationships, clarify the contamination dynamics and assess the impact of improvement measures. Serotype distribution was as follows: 1/2c (57.6%), 1/2b (18.7%), 4b (12.9%), 1/2a (6.5%) and 4a/4c (4.3%). Thirteen clones were simultaneously isolated in different butcher shops; 73.5% of establishments shared the same beef supplier. Cross-contamination was detected in L. monocytogenes-positive samples from 20% of butcher shops, mostly at the evaluation stage (91.7%). Up to five strains were isolated from each butcher shop at the evaluation (37%) and verification (22%) stages. Seven persistent clones were isolated over the three-year study period. Serotypes 4b and 1/2b significantly decreased during the evaluation stage. Although part of the contamination with L. monocytogenes was introduced by the beef supplier, the pathogen spread profusely in butcher shops, suggesting the relevance of keeping good hygiene control and management of the environment to prevent the spread of L. monocytogenes in butcher shops.